2015
DOI: 10.1007/s13353-015-0276-7
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining chicken primordial germ cells used for gene transfer: in vitro and in vivo results

Abstract: Recently, several attempts have been made to create a generation of transgenic chickens via chimeric intermediates produced by primordial germ cells (PGCs) transfer. This study aimed to compare the influences of different chicken PGCs isolated from circulating blood (bPGCs) or gonads (gPGCs), purification (ACK, Percoll or trypsin) and transfection methods (electroporation or lipofection) on the expression of transgenes in vitro and the migration of modified donor cells to the recipient gonads. The highest aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…It was initially incepted in the 1990s in the USA to automatically vaccinate chicks against Marek's disease and Gumboro disease in poultry . Since then, it has been used for a much wider application in order to stimulate embryonic development, immunological response, and beneficial probiotic bacteria . Casas‐Perez and Edens found that the administration of probiotics (lactic acid bacteria) via the in ovo technique, should be done on the 18th day of incubation.…”
Section: Basics Of In Ovo Technologymentioning
confidence: 99%
“…It was initially incepted in the 1990s in the USA to automatically vaccinate chicks against Marek's disease and Gumboro disease in poultry . Since then, it has been used for a much wider application in order to stimulate embryonic development, immunological response, and beneficial probiotic bacteria . Casas‐Perez and Edens found that the administration of probiotics (lactic acid bacteria) via the in ovo technique, should be done on the 18th day of incubation.…”
Section: Basics Of In Ovo Technologymentioning
confidence: 99%
“…In this stage, PGCs can be commonly acquired through gonad isolation and trypsinization. PGCs can transmit genetic information to next generations and are thus ideal for creating transgenic or gene-edited chickens (Bednarczyk et al 2002;Bednarczyk et al 2003; Van de Lavoir et al 2006;Naito 2015;Chojnacka-Puchta et al 2015;Sawicka et al 2015;Oishi et al 2016;Dimitrov et al 2016). However, PGCs are characterized by their low ability to induce effective and persistent transfection.…”
Section: Introduction To Editing Methods In Chickensmentioning
confidence: 99%
“…Germline cells identify, cell culture, and induction with retinoic acid (RA) PGC colonies were identi ed using a mouse anti-chicken c-KIT antibody (1:50) as a primary antibody and goat-anti-mouse FITC-conjugated IgM (1:50) as a secondary antibody (both from Santa Cruz Biotechnology, Santa Cruz, CA, USA). The identi ed PGCs were subjected to periodic acid Schiff (PAS) staining as previously described [12]. Brie y, PGCs were xed in 4% paraformaldehyde for 5 min, rinsed twice with 1 × PBS (Hyclone, South Logan, UT, USA), immersed in periodic acid solution for 5 min, washed with 1 × PBS, immersed in Schiff's solution for 15 min, washed twice in 1 × PBS, and observed under an inverted microscope.…”
Section: Animalsmentioning
confidence: 99%